The Record Management: Upcoming Challenges and Key Components to Enhancing Better Public Services - Muhamad Yusuf Yusuf; Denok Kurniasih Kurniasih; Paulus Israwan Setyoko (Jurnal Manajemen Pelayanan Publik, 2023)
This study observes the significance of record management in enhancing public services and identifies obstacles and supporting components associated with effective record management in the public sector. Literature review from articles in the Scopus database on record management in the public sector. Based on an analysis of the value of record management and lessons learned from previous difficulties, this study forecasts some upcoming record management challenges. These include the high volume of documents recorded and how it is stored, maintained, and protected; decentralized system by agencies; limited resources support including lack of capabilities staff and minimum quality of information and communications technology (ICT) and funding. Additionally, this analysis discovered that record management in public services has some supporting components. It consists of highly skilled trained personnel; proper standardization; and legal framework; well-developed ICT centralized system.